The assessment and validation of the depression, anxiety, and stress scale (DASS-21) among frontline doctors in Pakistan during fifth wave of COVID-19 - Muhammad Umar Nadeem; Steve J. Kulich; Ijaz Hussain Bokhari (Frontiers in Public Health, 2023)
ObjectiveThe study aims to document sociodemographic features, address the symptoms and levels of depression, anxiety, and stress among frontline doctors in Pakistan, and validate the depression, anxiety, stress scale (DASS-21) on the context of Pakistan.MethodA cross-sectional survey was conducted throughout the regions of Pakistan on frontline doctors to document their sociodemographic patterns and the levels of depression, anxiety, and stress while dealing with the fifth wave (Omicron-variant) of the coronavirus (SARS-CoV-2) pandemic in Pakistan (December 2021–April 2022). Respondents (N = 319) were recruited through a snowball sampling process.ResultsThough previous literature reported declines in psychological symptoms after earlier waves of COVID-19, these DASS-21 findings show that as the pandemic has worn on, frontline doctors in Pakistan are having considerable personal symptoms of depression (72.7%), anxiety (70.2%), and stress (58.3%). Though specifically related to the COVID-19 pandemic, they rated only moderate levels of depression and stress, however they reported severe levels of anxiety. The results also revealed a positive correlation between depression and anxiety (r = 0.696, p < 0.001), depression and stress (r = 0.761, p < 0.001), and anxiety and stress (r = 0.720, p < 0.001).ConclusionThrough the application of all required statistical procedures, DASS-21 is validated in the cultural context of Pakistan among this group of frontline doctors. The findings of this study can provide new directions for the policy makers (government and hospitals' administration) of Pakistan to focus on the mental wellbeing of the doctors under similar enduring public health crises and to protect them from short- or long-term disorders.